THE CHANGES OF MR. DARCY IN THE NOVEL PRIDE AND PREJUDICE BY JANE AUSTEN = SỰ THAY ĐỔI CỦA DARCY TRONG TIỂU THUYẾT KIÊU HÃNH VÀ ĐỊNH KIẾN CỦA JANE AUSTEN - Nguyễn, Huyền Ly (2020)
This article mainly describes the image of Mr. Darcy before and after he falls in love with Elizabeth. These “images” would be discussed in two separated part so that readers can distinguish the differences easily. This research will consist of interpreting, comparing and contrasting the sources of material that the researcher gets. After having adequate knowledge and data, the researcher will analyze and synthetize these sources of information and draw conclusion. The reasons for the transformation, the process of the changes will be discussed as well to find out the significance of the entire progression.